Polyvinylnorbornene Gas Separation Membranes - Dujardin, Wouter; Van Goethem, Cédric; Steele, Julian A.; Roeffaers, Maarten; Vankelecom, Ivo F. J.; Koeckelberghs, Guy (Polymers, 2019)
Polynorbornenes are already used in a wide range of applications. They are also considered materials for polymer gas separation membranes because of their favorable thermal and chemical resistance, rigid backbone and varied chemistry. In this study, the use of 5-vinyl-2-norbornene (VNB), a new monomer in the field of gas separations, is investigated by synthesizing two series of polymers via a vinyl-addition polymerization. The first series investigates the influence of the VNB content on gas separation in a series of homo and copolymers with norbornene. The second series explores the influence of the crosslinking of polyvinylnorbornene (pVNB) on gas separation. The results indicate that while crosslinking had little effect, the gas separation performance could be fine-tuned by controlling the VNB content. As such, this work demonstrates an interesting way to significantly extend the fine-tuning possibilities of polynorbornenes for gas separations.